Factor completely.

36, minus, y, squared
36−y
2

1 answer

To factor the expression \(36 - y^2\), we recognize that it is a difference of squares. The difference of squares can be factored using the formula:

\[ a^2 - b^2 = (a - b)(a + b) \]

In this case, we can identify \(a^2 = 36\) and \(b^2 = y^2\). Thus, we have:

\[ a = 6 \quad (\text{since } 6^2 = 36) \] \[ b = y \]

Now we can apply the difference of squares formula:

\[ 36 - y^2 = 6^2 - y^2 = (6 - y)(6 + y) \]

Therefore, the completely factored form of \(36 - y^2\) is:

\[ \boxed{(6 - y)(6 + y)} \]